Product Quality Perception of Former Centrally Planned EU Countries' Imports and Exports - Vincenzo Merella; Josef Taušer (Prague University of Economics and Business, Faculty of International Relations (FIR), 2022)
After Comeconís dissolution, agentsí lack of experience in product dierentiation could have triggered demand-side mechanisms affecting trade flows between the two sides of the fallen Iron Curtain. Specifically, producers from a block of countries might have faced a quality perception gap when exporting to the other block. We investigate this issue empirically by examining EU custom data. Our findings are consistent with products originating from former centrally planned countries being penalized by consumers from established decentralized economies. The magnitude of this effect lowers over time and vanishes when we consider extra-EU exporters. The evidence aligns with psychology and marketing contributions and may have important implications for the literature on international trade and economic development dealing with quality dierentiation and foreign direct investment.
Keywords: F10; F40; P20; 330; Developing Countries; EU; Former Centrally Planned Countries; Import Origin; International Trade; Market Segmentation; Nonhomothetic preferences; Pricing-to-market; Product Quality Perception